Black phosphorus crystal as a saturable absorber for both a Q-switched and mode-locked erbium-doped fiber laser. Issue 76 (1st August 2016) - Ismail, E. I.; Kadir, N. A.; Latiff, A. A.; Ahmad, H.; Harun, S. W.
Abstract : We report a simple way to generate Q-switched and mode-locked pulses by incorporating black phosphorus (BP) as a saturable absorber (SA) in an erbium-doped fiber laser (EDFL) cavity. Abstract : We report a simple way to generate Q-switched and mode-locked pulses by incorporating black phosphorus (BP) as a saturable absorber (SA) in an erbium-doped fiber laser (EDFL) cavity. The preparation of BP-based SA is facilitated by a mechanical exfoliation method. Stable mode-locked pulses with a repetition rate of 1 MHz and energy of 7.35 nJ energy per pulse are generated under a maximum pump power of 250 mW in the ring cavity.